Eye of the beholder - Bamford, Emma (Scout Press, 2024)
When Maddy Wight is hired to ghostwrite the memoir of world-renowned cosmetic surgeon Dr. Angela Reynolds, she thinks it might just be her chance to get her career back on track. She travels to Angela's remote estate in the Scottish Highlands to hunker down and learn everything she can. But the deeper she digs, the more elusive the doctor becomes. Is there more hidden beneath the surface of the kaleidoscopic beauty industry than Angela wants to reveal? Sharing the estate is Angela's enigmatic business partner, Scott, whose mercurial moods change as quickly as the conditions on the darkening moors outside. Confined to the glass-walled house, Maddy can't shake the feeling of being watched. As objects go missing, handprints appear on the windows, and a stranger lurks in the grounds, she finds herself drawn ever closer to Scott. Returning to London once the book is finished, Maddy is excited for their future together. But her dreams are shattered at the book launch when Angela learns that Scott has leapt to his death from the Scottish cliffs. Which is why, months later and lost in a fog of grief, Maddy is completely blindsided when she sees Scott entering the Tube station just in front of her. It can't be him, can it? After all, Scott is dead... or is he? --